Characterisation of basic water balance parameters of Debrecen - Guizani, Douraied; Budayné Bódi, Erika; Tamás, János; Nagy, Attila (Acta Agraria Debreceniensis, 2022)
This work aims to develop a hydrological modelling tool to help managers make the right decisions for Debrecen, in the face of water scarcity and the increase in agricultural and domestic needs over time. The methodology was based on the creation of a climatic database, at monthly time steps, from 2016 to 2019, and cartographic (land use, digital elevation model, and hydrological network). As a next step, the watershed was delimitated into sub-basins to determine the shape and the physiographic characteristics of sub-watersheds. Finally, a hydrological study was prepared by calculating the time of concentration to build a database of water resources in the study area. This water resource will be used as an input parameter for urban farming.